The use of participatory systems mapping as a research method in the context of non-communicable diseases and risk factors: a scoping review - Amber van den Akker; Alice Fabbri; Dima I. Alardah; Anna B. Gilmore; Harry Rutter (BMC, 2023)
Abstract Context Participatory systems mapping is increasingly used to gain insight into the complex systems surrounding non-communicable diseases (NCDs) and their risk factors. Objectives To identify and synthesize studies that used participatory systems mapping in the context of non-communicable diseases. Design Scoping review. Eligibility criteria Peer-reviewed studies published between 2000 and 2022. Study selection Studies that focused on NCDs and/or related risk factors, and included participants at any stage of their system's mapping process, were included. Categories for analysis The main categories for analysis were: (1) problem definition and goal-setting, (2) participant involvement, (3) structure of the mapping process, (4) validation of the systems map, and (5) evaluation of the mapping process. Results We identified 57 studies that used participatory systems mapping for a variety of purposes, including to inform or evaluate policies or interventions and to identify potential leverage points within a system. The number of participants ranged from 6 to 590. While policymakers and professionals were the stakeholder groups most often included, some studies described significant added value from including marginalized communities. There was a general lack of formal evaluation in most studies. However, reported benefits related mostly to individual and group learning, whereas limitations described included a lack of concrete actions following from systems mapping exercises. Conclusions Based on the findings of this review, we argue that research using participatory systems mapping would benefit from considering three different but intertwined actions: explicitly considering how different participants and the power imbalances between them may influence the participatory process, considering how the results from a systems mapping exercise may effectively inform policy or translate into action, and including and reporting on evaluation and outcomes of the process, wherever possible.